Level five of leadership and its role in achieving organizational well-being - Darwish, Sanhwit; Daoud, Ranaj (Humanities Journal of University of Zakho, 2023)
The research aims to present the concept of the fifth level of leadership as one of the most important contemporary orientations in leadership and its role in organizational well-being as an umbrella which cover all positive aspects that create the appropriate climate for performance, success and excellence for the organization. The research depends on the descriptive analytical approach to test the hypothesis of the correlation between the fifth level of leadership among administrative leaders and organizational well-being among respondents, as well as the hypothesis of the fifth level of leadership dimensions on organizational well- being in Universities in Duhok governorate. The sample included (141) of faculty members in these Universities who answered the questionnaire, which was the main tool for data collection. The data were analyzed based on a number of statistical tools, and the research reached results, including the existence of a correlation between the fifth level of leadership And organizational well-being, and that organizational well-being is positively affected by the fifth level of leadership. The research concluded with the need to adopt the dimensions that represent the fifth level of leadership among administrative leaders in universities, as well as recommending some titles for future studies that serve the organizational field.